An Efficiency Analysis of Banks in Indonesia - HUANG, YINGYING (2019)
Indonesia plays as the largest economy in Southeast Asia so that it is not impossible to be influenced by the international economic environment (World Bank, 2019). The banking industry has a significant impact on the Indonesian economy and has experienced several changes over the past decades. The study will describe the Indonesian banking system and use the concept of cost efficiency to analyze how efficient are banks in Indonesia. Meanwhile, the study will try to find the determinants and explain why they can influence bank efficiency.